Sixty years of forensic seismology at AWE Blacknest. Issue 4 (1st August 2021) - Green, David; Heyburn, Ross; Keeble, Jessica; Nippress, Alexandra; Nippress, Stuart; Peacock, Sheila; Young, John
Abstract : David Green, Ross Heyburn, Jessica Keeble, Alexandra Nippress, Stuart Nippress, Sheila Peacock and John Young review the history of the UK's seismological monitoring of underground nuclear testing Abstract: David Green, Ross Heyburn, Jessica Keeble, Alexandra Nippress, Stuart Nippress, Sheila Peacock and John Young review the history of the UK's seismological monitoring of underground nuclear testing